Assertive and Expressive Speech Act Used by English Teachers and Its Implications - Rezky Uspayanti (LETS: Journal of Linguistics and English Teaching Studies, 2022)
This study focused on the use of assertive and expressive speech acts by English teachers and its’ implication in teaching and learning process. The study was done in Senior High School 1 Pinrang. The sample was two English teachers. The sample was taken by using a purposive sample. The sample was chosen because they produced more speech acts in teaching and learning process. In collecting the data, classroom recording, observation checklist and interview were used. In analyzing data from classroom recording and interview, the researcher used qualitative data analysis that consisted of three stages: data reduction, data display and conclusion drawing/verification. The results show that teacher A and B used representative and expressive speech act with a different function. Teacher A used representative speech acts which functions were informing, explaining, asserting and concluding the material, while teacher B used representative speech acts which functions were explaining, informing and asserting the material. For expressive speech act, teacher A used expressive speech acts which functions were greeting, apologizing and pleasure or happy feeling, while teacher B used expressive speech acts in classroom interaction which functions were greeting, taking students’ attention, apologizing, and pleasure in terms of thanking. For implication of speech acts are as the way in making the students understood on the teacher’s explanation and used English properly. Therefore, it is also as the way to motivate the students, avoid the misunderstanding in learning process, build up the effective communication build up their understanding, know the communicative functions, stimulate each other and would be used to hear and use English.